Allergen immunotherapy for birch pollen-allergic patients: recent advances. (May 2016) - Moingeon, Philippe; Floch, Véronique Bordas-Le; Airouche, Sabi; Baron-Bodo, Véronique; Nony, Emmanuel; Mascarell, Laurent
As of today, allergen immunotherapy is performed with aqueous natural allergen extracts. Recombinant allergen vaccines are not yet commercially available, although they could provide patients with well-defined and highly consistent drug substances. As Bet v 1 is the major allergen involved in birch pollen allergy, with more than 95% of patients sensitized to this allergen, pharmaceutical-grade recombinant Bet v 1-based vaccines were produced and clinically tested. Herein, we compare the clinical results and modes of action of treatments based on either a birch pollen extract or recombinant Bet v 1 expressed as hypoallergenic or natural-like molecules. We also discuss the future of allergen immunotherapy with improved drugs intended for birch pollen-allergic patients suffering from rhinoconjunctivitis.